Indirect calorimetry of metabolic rate in college-age Japanese subjects during various office activities - Nomoto, Akihisa; Hisayama, Ryo; Yoda, Shu; Akimoto, Mizuho; Ogata, Masayuki; Tsutsumi, Hitomi; Tanabe, Shin-ichi (Building and environment, 2021)
Indoor climate regulations are based on an empirical thermal comfort model developed in the 1960s. The standard values for one of its fundamental parameters, which is the metabolic rate, is based on the data pertaining to European and North American men measured at that time and may overestimate the metabolic rate of modern Japanese, especially women. Therefore, applying standard values to modern Japanese may lead to inaccurate thermal comfort evaluation. The purpose of this research is to investigate the metabolic rates of Japanese individuals performing different office activities using accurate body surface area data in order to determine whether there exist differences between the measured and standard values. Three-dimensional measurements of the body surface area and indirect calorimetry were applied to determine their metabolic rates accurately. This study measured the mean metabolic rates of 45 college-age Japanese subjects while they were sitting quietly, sitting and typing, standing quietly, and standing and typing at 0.9 and 0.8 met, respectively, and 2.6 met each while they were walking at a speed of 4.0 km/h. These values are significantly lower than the standard values specified in the current international standards for all activity levels. Moreover, females exhibited lower metabolic rates than males, and significant differences between both biological sexes were found for all activity levels excluding walking. It was found that applying the metabolic rate values specified in the existing thermal comfort standards to college-age Japanese, particularly females, can lead to inaccurate thermal comfort evaluation and CO2 generation rate estimation for building occupants. •Metabolic rate of college-age Japanese subjects during various office activities was measured.•Three-dimensional body surface scanning and indirect calorimetry were applied.•Measured mean metabolic rates were significantly lower than values in standards.•Metabolic rates in females were lower than those in males.•Effects of inaccurate metabolic rate on thermal comfort and CO2 generation rate were illustrated.